LEXICAL AND GRAMMATICAL COMPARISON OF FUNCTIONAL-SEMANTIC FIELD OF BILOGICAL SEX IN RUSSIAN LINGUISTICS - Reşat ŞAKAR (Fırat University, 2019)
In this article, It is studied whether a monocentric or a polycentric forms the basis of the structure of the functional semantics field of biological sex in Russian Linguistics, and in this functional semantics field it is revealed what sort of role the lexical components have in functional and semantic fields. As A.V Bondarko has defined, functional semantic field,which emerges as a semantic category by grouping of language tools in different levels, is characterised as one of the basic terms of functional grammar. And also as A.V Bondarko has pointed out , this functional semantics field splits into two as monocentric and polycentric. Th centric of monocentric functional semantic field is formed just by a grammar category such as verb, adjective e.t.c. while the centric of polycentric functional semantics field is formed by being used of different categories of grammar such as verb and tense, noun and adjective. Although A.V Bondarko hasn't stated the semantic categories,forming the essence of the functional semantics field, as noun categories such as biological sex and living / non-living beings, especially S.G Mameckov, handling the functional semantics field of biological sex as completely different and as an independent field category, scrutinizes it in his thesis study. According to S.G Mameckov, functional semantic field of biological sex is a polycentric field type. Polycentric type